Preparation and performance investigation of a high efficiency cement permeation type waterproofing materials. (15th February 2023) - Liu, Peng; Liu, Menglu; Sha, Fei; Chen, Ying; Zhi, Weiting; He, Sasa; Yu, Zhiwu
Highlights: A novel cement permeation type waterproofing materials was prepared. Compositions of the active chemicals were determined. Mechanical properties of specimens with and without CCCW were tested. Extensibility, water absorption and impermeability tests of CW were proceeded. Optimal content of CCCW was proposed. Abstract: The active chemicals play the primary waterproof role in Cementitious Capillary Crystalline Waterproofing Materials (CCCW). Based on the combined mechanism of precipitation reaction and complexation precipitation reaction, precipitation component, complexing agent, calcium ion compensator, surfactant, and defoaming agents were determined as the composition of the active chemicals in this study. Based on the multiple performance tests, the material components and the content of active chemicals were investigated with the single and orthogonal factors. The results showed that with the increase of sodium silicate content, the flexural and compressive strengths of the specimens at 28 d increased, and the water absorption of the specimens gradually decreased. When the sodium silicate content was 2 wt%, the flexural and compressive strengths of the specimens at 28 d increased by 55% and 16%, respectively, and the water absorption of the specimens decreased by 27%. When the content of the complexing agent was constant, the setting time of the specimen gradually prolonged with the increase of the proportion of the hydroxyl and carboxyl groups in the molecular structure. Meanwhile, the flexural and compressive strengths of the specimen decreased gradually with the increase of the content of the complexing agent. With the increase of calcium formate content, the strength of the specimens tended to increase first and then decrease. When the ratio between calcium formate and calcium hydroxide was 10:90, the compressive strength of the specimens cured for 28 d increased by 42%. Based on the analysis of the mechanical properties, water absorption, and expansion of the specimen under orthogonal factors, the mixing ratio of the active chemicals was: precipitation component 2 wt%, complexing agent 1 wt%, calcium ion compensator 3 wt%, surfactant 1.5 wt%, and defoaming agents 0.7 wt%. The impermeability pressure ratios of specimens with and without CCCW coating reached to 275% and 200% at 28 d, respectively. The water resistance of the specimens increased with the increase of curing age, and the water absorption of the specimen was reduced by 56% at 28 d.